Assessment of Transporter‐Mediated Drug Interactions for Enasidenib Based on a Cocktail Study in Patients With Relapse or Refractory Acute Myeloid Leukemia or Myelodysplastic Syndrome. (27th October 2021) - Cheng, Yiming; Wang, Xiaomin; Tong, Zeen; Reyes, Josephine; Carayannopoulos, Leon; Zhou, Simon; Li, Yan
Abstract: As a first‐in‐class, selective, potent inhibitor of the isocitrate dehydrogenase‐2 (IDH2) mutant protein, enasidenib was approved by the US Food and Drug Administration in 2017 for the treatment of adult patients with relapsed or refractory acute myeloid leukemia with an isocitrate dehydrogenase‐2 mutation. An in vitro study showed that enasidenib at clinically relevant concentrations has effects on multiple drug metabolic enzymes and transporters, including inhibition of P‐glycoprotein, breast cancer resistance protein, organic anion transporter (OAT) P1B1, and OATP1B3 transporters. Therefore, a drug‐drug interaction study was conducted to assess the impact of enasidenib at steady state on the pharmacokinetics of several probe compounds in patients with relapsed or refractory acute myeloid leukemia or myelodysplastic syndrome, including the probes herein described in this article, digoxin and rosuvastatin. Results from 8 patients (all Asian) with a mean age of 67.1 years showed that following coadministration of enasidenib (100 mg, 28‐day once‐daily schedule) for 28 days (at steady state), digoxin's (0.25 mg) area under the plasma concentration–time curve from time 0 to 30 days was 1.2‐fold (90% confidence interval, 0.9‐1.6), compared with digoxin alone. Following coadministration of enasidenib (100 mg, 28‐day once‐daily schedule) for 28 days (at steady state), rosuvastatin's (10 mg) area under the plasma concentration–time curve from time 0 to infinity was 3.4‐fold (90% confidence interval, 2.6‐4.5) compared with rosuvastatin alone. These results should serve as the basis for dose recommendations for drugs that are substrates of P‐glycoprotein, breast cancer resistance protein, OATP1B1, and OATP1B3 transporters, when used concomitantly with enasidenib.